Stability analysis of linear impulsive differential systems under structural perturbation - Martynyuk, A. A.; Stavroulakis, I. P. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
The stability and asymptotic stability of solutions of large-scale linear impulsive systems under structural perturbations are investigated. Sufficient conditions for stability and instability are formulated in terms of the fixed signs of special matrices.